2012
DOI: 10.1016/j.ajhg.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

SKIV2L Mutations Cause Syndromic Diarrhea, or Trichohepatoenteric Syndrome

Abstract: Syndromic diarrhea (or trichohepatoenteric syndrome) is a rare congenital bowel disorder characterized by intractable diarrhea and woolly hair, and it has recently been associated with mutations in TTC37. Although databases report TTC37 as being the human ortholog of Ski3p, one of the yeast Ski-complex cofactors, this lead was not investigated in initial studies. The Ski complex is a multiprotein complex required for exosome-mediated RNA surveillance, including the regulation of normal mRNA and the decay of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
124
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 20 publications
1
124
0
4
Order By: Relevance
“…Mutations in SKI complex genes have been linked to tricho-hepato-enteric (THE) syndrome, which causes intestinal failure (Hartley et al 2010;Fabre et al 2012Fabre et al , 2013. In addition, mutations in the DIS3 catalytic subunit gene have been implicated in multiple myeloma (Chapman et al 2011;Tomecki et al 2013;Robinson et al 2015).…”
mentioning
confidence: 99%
“…Mutations in SKI complex genes have been linked to tricho-hepato-enteric (THE) syndrome, which causes intestinal failure (Hartley et al 2010;Fabre et al 2012Fabre et al , 2013. In addition, mutations in the DIS3 catalytic subunit gene have been implicated in multiple myeloma (Chapman et al 2011;Tomecki et al 2013;Robinson et al 2015).…”
mentioning
confidence: 99%
“…Buscaron mutaciones en el gen ortólogo humano de SKI3 que resultó en la identificación de mutaciones deletéreas en el gen SKIV2L en los seis individuos referidos. 5 En el Cuadro 1 se resumen los hallazgos de estos autores con los datos observados en nuestra paciente. Ellos mismos señalan otro gen candidato para los casos potenciales donde la pesquisa de mutaciones conocidas sea negativa: el gen WDR61, ortólogo humano del tercer cofactor SKI8.…”
Section: Discussionunclassified
“…Two are very frequent (more than 90%): IUGR and immunodeficiency; 2 are frequent: skin abnormalities and liver disease and 2 are rare: congenital cardiac defects and platelet anomaly. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The phenotypic presentation of THE-S is heterogeneous, and ranges from mild to severe form, which is characterized with long-term parenteral nutrition, and in some patients, typically it lasts for months to years, to achieve adequate nutrition and growth. 12 However, longterm parenteral nutrition should not be started in patients with concomitant liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 44 cases have been published between 1982 and 2012. Literature reviewed showed that 9 clinical signs are associated with THE-S. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Three are constant: intractable diarrhea, facial dysmorphism and hair abnormality. Two are very frequent (more than 90%): IUGR and immunodeficiency; 2 are frequent: skin abnormalities and liver disease and 2 are rare: congenital cardiac defects and platelet anomaly.…”
Section: Discussionmentioning
confidence: 99%